Billingualism and Cultural Identity: An Impact Analysis of the Use of Sundanese and Indonesian among Adolescents in Pandeglang - Siti Nurmalihah; Nuni Nurhasanah; Alfina Melani; Eneng Liah Khoiriyah (Hikamatzu | Journal of Multidisciplinary, 2025)
Bilingualism is a prevalent phenomenon in Pandeglang, Banten, where teenagers navigate between the local Sundanese language and the national Indonesian language in various social contexts. This study aims to explore how bilingualism influences the cultural identities of youth in this region. Through qualitative methods, including in-depth interviews and participatory observations, data were collected from 20 teenagers aged 15-18. The study reveals that the use of Sundanese primarily occurs in informal family settings, while Indonesian dominates formal settings like school and public media. Additionally, both languages are creatively integrated in digital spaces, such as social media, where local identity is expressed through Sundanese, and broader national identity through Indonesian. However, challenges in maintaining Sundanese due to the dominance of Indonesian, particularly in urban areas, were noted. The study concludes that bilingualism serves as a bridge between local and national identities, but the sustainability of Sundanese is threatened without strategic interventions, such as incorporating it into formal education and leveraging digital platforms for cultural preservation.